The phenotypic and molecular genetic spectrum of Alstrom syndrome in 44 Turkish kindreds and a literature review of Alstrom syndrome in Turkey - ELÇİOĞLU, HURİYE NURSEL (NATURE PUBLISHING GROUP, 2015)
Alstrom syndrome (ALMS) is an autosomal recessive disease characterized by multiple organ involvement, including neurosensory vision and hearing loss, childhood obesity, diabetes mellitus, cardiomyopathy, hypogonadism, and pulmonary, hepatic, renal failure and systemic fibrosis. Alstrom Syndrome is caused by mutations in ALMS1, and ALMS1 protein is thought to have a role in microtubule organization, intraflagellar transport, endosome recycling and cell cycle regulation. Here, we report extensive phenotypic and genetic analysis of a large cohort of Turkish patients with ALMS. We evaluated 61 Turkish patients, including 11 previously reported, for both clinical spectrum and mutations in ALMS1. To reveal the molecular diagnosis of the patients, different approaches were used in combination, a cohort of patients were screened by the gene array to detect the common mutations in ALMS1 gene, then in patients having any of the common ALMS1 mutations were subjected to direct DNA sequencing or next-generation sequencing for the screening of mutations in all coding regions of the gene. In total, 20 distinct disease-causing nucleotide changes in ALMS1 have been identified, eight of which are novel, thereby increasing the reported ALMS1 mutations by 6% (8/120). Five disease-causing variants were identified in more than one kindred, but most of the alleles were unique to each single patient and identified only once (16/20). So far, 16 mutations identified were specific to the Turkish population, and four have also been reported in other ethnicities. In addition, 49 variants of uncertain pathogenicity were noted, and four of these were very rare and probably or likely deleterious according to in silico mutation prediction analyses. ALMS has a relatively high incidence in Turkey and the present study shows that the ALMS1 mutations are largely heterogeneous; thus, these data from a particular population may provide a unique source for the identification of additional mutations underlying Alstrom Syndrome and contribute to genotype-phenotype correlation studies.
Keywords: DILATED CARDIOMYOPATHY; RARE CAUSE; ALMS1; MUTATIONS; OBESITY; INVOLVEMENT; DIAGNOSIS; DISEASES